Financiamento coletivo e participação de fãs na sustentabilidade do jornalismo de RPG : um estudo de caso sobre a revista Dragão Brasil - Camelo, Diogo de Almeida (2024)
This research aims to investigate how crowdfunding and changes in cultural industries have led to transformations in specialized pop culture magazines. To achieve this, we conducted a case study of Dragão Brasil (DB), the most successful RPG (Tabletop Role-Playing Games) magazine in Brazil, which actively involves readers and analog game fandom groups. The theoretical-methodological perspective of this master’s thesis is grounded in the following central questions: how do innovative forms of magazine journalism financing, such as in the case of Dragão Brasil, emerge, and how do these initiatives structure the journalistic field and engage their audiences to achieve sustainability? To answer these questions, we traced the history of RPG magazines and their immersion in convergence culture through transmedia narratives and exploration of fan labor by publishers, based on studies of participatory culture. We delved into Dragão Brasil magazine by intersecting studies of magazine journalism, game journalism, and pop culture journalism, conducting a survey on the history of the periodical and its relationship with fans through interviews with key individuals from the DB publisher and a questionnaire distributed to fans who financially support the magazine through recurring crowdfunding campaigns. The results indicate that the trust relationship between producers and consumer-fans of products created and expanded through the magazine itself seems to be the key to the success of crowdfunding initiatives in cultural journalism. The active participation of consumers benefits not only them, as they become part of the production, but also the producers, who gain from the strengthened image of their products promoted by fan communities. This relationship is intrinsic to the editorial and commercial practices of the magazine, which, by endorsing a sense of participatory community, renew the values of digital culture.